Developing the US Wildland Fire Decision Support System - Erin K. Noonan-Wright; Tonja S. Opperman; Mark A. Finney; G. Thomas Zimmerman; Robert C. Seli; Lisa M. Elenz; David E. Calkin; John R. Fiedler (Journal of Combustion)
A new decision support tool, the Wildland Fire Decision Support System (WFDSS) has been developed to support risk-informed decision-making for individual fires in the United States. WFDSS accesses national weather data and forecasts, fire behavior prediction, economic assessment, smoke management assessment, and landscape databases to efficiently formulate and apply information to the decision making process. Risk-informed decision-making is becoming increasingly important as a means of improving fire management and offers substantial opportunities to benefit natural and community resource protection, management response effectiveness, firefighter resource use and exposure, and, possibly, suppression costs. This paper reviews the development, structure, and function of WFDSS, and how it contributes to increased flexibility and agility in decision making, leading to improved fire management program effectiveness.